If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4v + 6 = 2v + -4 Reorder the terms: 6 + 4v = 2v + -4 Reorder the terms: 6 + 4v = -4 + 2v Solving 6 + 4v = -4 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. 6 + 4v + -2v = -4 + 2v + -2v Combine like terms: 4v + -2v = 2v 6 + 2v = -4 + 2v + -2v Combine like terms: 2v + -2v = 0 6 + 2v = -4 + 0 6 + 2v = -4 Add '-6' to each side of the equation. 6 + -6 + 2v = -4 + -6 Combine like terms: 6 + -6 = 0 0 + 2v = -4 + -6 2v = -4 + -6 Combine like terms: -4 + -6 = -10 2v = -10 Divide each side by '2'. v = -5 Simplifying v = -5
| -8(k-2)-6(k-8)=22 | | 5(w+9)=49 | | 3x-5.46=-3.87 | | 2x+18=-2y+12 | | 5.5-8.1=x | | ax+28x= | | -10+1=q | | -5t-2(-5t+10)=100 | | -8(-8-6)=-6-22 | | 4x-5=5x-7 | | 12=-6z-6 | | x^3+13=-14 | | -5(9+a)=10 | | 44=t-20 | | 383=8x+7 | | 9=4(5-a) | | 10x+6=6x-3 | | -1(x+8)+9=7x+1-8x | | 2z=19.9 | | -11-5=6(5+4) | | -12=-2p+8 | | 12(3x-7)=-300 | | 2q=3 | | 3q+7=7q | | 0=6x+8 | | (X+0.2)(X+1.5)=0 | | 7q^2-9q-(n+2)=0 | | -4n+9=-7 | | -14+28=-2(x+6) | | 3x=360/4 | | 5(x+12)+7=11 | | 329-9x=14 |